2019
DOI: 10.1002/cam4.2179
|View full text |Cite
|
Sign up to set email alerts
|

Necessity of concurrent chemotherapy in N2‐3 nasopharyngeal carcinoma treated with neoadjuvant chemotherapy of ≥3 cycles followed by intensity‐modulated radiotherapy

Abstract: Concurrent chemotherapy (CCT) is used in locally advanced nasopharyngeal carcinoma (NPC) for improved local control, which could also be achieved by intensity‐modulated radiotherapy (IMRT). And for N2‐3 NPC, distant metastasis is the more important cause of death. This study aims to evaluate the value of CCT in N2‐3 NPC when neoadjuvant chemotherapy (NACT) of sufficient cycles is performed to eradicate distant metastasis. It enrolled 959 patients diagnosed with TxN2‐3M0 NPC from July 2011 to December 2015 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 31 publications
0
11
0
Order By: Relevance
“…Levy et al [24] also reported that the highest morbidity of acute toxicity was dermatitis (97%) with concurrent radiotherapy and cetuximab after taxane-based induction chemotherapy in locally advanced head and neck cancer. Concurrent chemotherapy in NPC treated with neoadjuvant chemotherapy followed by IMRT was exhibited 48.3% dermatitis, 49.2% oral mucositis, 38.1% bone marrow toxicity, 40.9% xerostomia and 21.2% nausea vomiting [25]. There are more than 40% of patients occurred severity acute injuries for most of locoregional advanced cancer during treatment in previous studies.…”
Section: Discussionmentioning
confidence: 93%
“…Levy et al [24] also reported that the highest morbidity of acute toxicity was dermatitis (97%) with concurrent radiotherapy and cetuximab after taxane-based induction chemotherapy in locally advanced head and neck cancer. Concurrent chemotherapy in NPC treated with neoadjuvant chemotherapy followed by IMRT was exhibited 48.3% dermatitis, 49.2% oral mucositis, 38.1% bone marrow toxicity, 40.9% xerostomia and 21.2% nausea vomiting [25]. There are more than 40% of patients occurred severity acute injuries for most of locoregional advanced cancer during treatment in previous studies.…”
Section: Discussionmentioning
confidence: 93%
“…24 Concurrent chemotherapy in NPC treated with neoadjuvant chemotherapy followed by IMRT was exhibited 48.3% dermatitis, 49.2% oral mucositis, 38.1% bone marrow toxicity, 40.9% xerostomia and 21.2% nausea vomiting. 25 There are more than 40% of patients occurred severity acute injuries for most of locoregional advanced cancer during treatment in previous studies. The investigation of IMRT dose distribution to the skin in head and neck squamous cell carcinoma was reported the incidence of grade 3 and 4 radiation dermatitis was 41.1% in patients included and 50% vs 36.6%…”
Section: Discussionmentioning
confidence: 99%
“…Levy et al also reported that the highest morbidity of acute toxicity was dermatitis (97%) with concurrent radiotherapy and cetuximab after taxane-based induction chemotherapy in locally advanced head and neck cancer 25 . Concurrent chemotherapy in NPC treated with neoadjuvant chemotherapy followed by IMRT was exhibited 48.3% dermatitis, 49.2% oral mucositis, 38.1% bone marrow toxicity, 40.9% xerostomia and 21.2% nausea vomiting 26 . There are more than 40% of patients occurred severity acute injuries for most of locoregional advanced cancer during treatment in previous studies.…”
Section: Discussionmentioning
confidence: 99%